2021
DOI: 10.1007/s10566-021-09623-3
|View full text |Cite
|
Sign up to set email alerts
|

Dominican, Salvadoran, and Chinese Immigrant Parents’ Reasoning About School Readiness Skills

Abstract: Background. The importance of parental beliefs and practices related to children's school readiness skills is widely documented, but few studies explicitly focus on immigrant families. Further, no known studies have examined immigrant parents' beliefs about what skills children need to be successful in kindergarten.Objectives. The overarching aim of this mixed-methods study was to investigate the school readiness beliefs of parents who are identified as immigrants in the United States. We examined the skills t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Previous studies yielded mixed results in terms of the association between SES and parents’ school-readiness beliefs ( Piotrkowski et al, 2000 ; Kim et al, 2005 ; Barbarin et al, 2008 ; Puccioni, 2015 ; Slicker et al, 2021 ; Sawyer et al, 2022 ). Among these studies, the results of the present study confirm the research findings of two studies ( Kim et al, 2005 ; Slicker et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies yielded mixed results in terms of the association between SES and parents’ school-readiness beliefs ( Piotrkowski et al, 2000 ; Kim et al, 2005 ; Barbarin et al, 2008 ; Puccioni, 2015 ; Slicker et al, 2021 ; Sawyer et al, 2022 ). Among these studies, the results of the present study confirm the research findings of two studies ( Kim et al, 2005 ; Slicker et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Such results are somewhat consistent with the mixed findings in previous variable-centered research exploring Chinese parents’ school-readiness beliefs, which showed that Chinese parents stress motivation and persistence ( Luo et al, 2013 ), or stress approaches to learning more than academic skills ( Zhang et al, 2008 ). In a recent person-centered study, Sawyer et al (2022) found that Chinese immigrant parents are more likely to attach great importance to learning-related skills, including approaches to learning and self-regulatory skills, rather than academic skills. Such findings support the patterns we identified in the two most prevalent subgroups in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations